Bertahan Sampai Kesudahan Akan Diselamatkan - Agustinus Faot; Jonathan Octavianus; Juanda Juanda; Daniel Ari Wibowo (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2019)
The case that is quite serious in theology is the doctrine of salvation, there is also a text which may confuse readers of the Bible if it does not have the ability to expose the Bible, Matthew 24:13, which can reveal that those who endure to the end are saved that, defense is an effort in every human being to strengthen himself or confirm life against all the problems he faces. It is important to note also that survival also does not always explain an active action to boast of itself, but surviving can be understood as a definite action subjected to actions by other people, other events. Then last into a passive position where people are required to be ready to bear claim, action or punishment; related to the concept of human salvation that God works fully. But there is a time when humans are obliged to survive. An idea more suitable to understand the text of Matthew 24:13, requires accurate observation of the Gospel of Matthew to understand actely the entire discussion from Matthew 24:13, must read and understand this paper from beginning to end. Because the questions relating to blessed salvation and those who survive in Matthew 24:13, are discussed in this scientific work.